2021
DOI: 10.1038/s41598-021-01831-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of good governance in the race for global vaccination during the COVID-19 pandemic

Abstract: Governments have developed and implemented various policies and interventions to fight the COVID-19 pandemic. COVID-19 vaccines are now being produced and distributed globally. This study investigated the role of good governance and government effectiveness indicators in the acquisition and administration of COVID-19 vaccines at the population level. Data on six World Bank good governance indicators for 172 countries for 2019 and machine-learning methods (K-Means Method and Principal Component Analysis) were u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 10 publications
2
25
0
1
Order By: Relevance
“…Within a global curative imaginary, access to vaccines represented survival not the “getting back to normal” of the Global North. While there are programmes such as COVID-19 Vaccines Global Access (COVAX) to ensure equitable global vaccine distribution, directed by GAVI, the Vaccine Alliance, the Coalition for Epidemic Preparedness Innovations, and the World Health Organisation (WHO), such international partnerships seemed to have to sucede urgency to national priorities which also protected pharmaceutical investments and distributions in the Global North (Tatar et al, 2021 ).…”
Section: Case-study 2: Learning To Live With Indeterminacies Of Cure:...mentioning
confidence: 99%
“…Within a global curative imaginary, access to vaccines represented survival not the “getting back to normal” of the Global North. While there are programmes such as COVID-19 Vaccines Global Access (COVAX) to ensure equitable global vaccine distribution, directed by GAVI, the Vaccine Alliance, the Coalition for Epidemic Preparedness Innovations, and the World Health Organisation (WHO), such international partnerships seemed to have to sucede urgency to national priorities which also protected pharmaceutical investments and distributions in the Global North (Tatar et al, 2021 ).…”
Section: Case-study 2: Learning To Live With Indeterminacies Of Cure:...mentioning
confidence: 99%
“…Recurrent waves of infection paired with more infectious virus variants are still placing a severe strain on public health systems, preventing governments from abolishing safety regulations and returning their countries to a pre-pandemic state. Potential explanations for recurrent infection waves include mutations of the virus that lead to (partial) evasion of vaccine-derived antibodies, anti-vaccination movements spreading misinformation, unsubstantiated rejection/fear of COVID-19 vaccines, conspiracy theories as well as mistrust in pharmaceutical companies or public institutions [ 12 , 13 , 14 , 15 , 16 , 17 ]. Aside from countering these obstacles, effective post-infection treatments are required to finally put a stop to the overload of hospitals, particularly intensive care units (ICUs).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, by 11 December 2020, the Food and Drug Administration [FDA] issued the first emergencyuse authorization for the mRNA-based BNT162b2 vaccine produced by Pfizer/BioNTech (New York, NY, USA) [5]. Weeks later, other vaccines came out, and by the first trimester of 2021, several countries began to massively vaccinate their population [6,7] (Table 1). The Pfizer Phase III study included over 46,000 participants globally, and the results found 95.0% efficacy in preventing infection 7 days after the second dose administration in participants, with these results being pivotal in the FDA granting an EUA for the vaccine in the US.14 On 31 March 2021, Pfizer and BioNTech announced remarkable 100% vaccine efficacy in young adolescents aged 12-15 years, after phase 1/2/3 trials [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, by 11 December 2020, the Food and Drug Administration [FDA] issued the first emergency-use authorization for the mRNA-based BNT162b2 vaccine produced by Pfizer/BioNTech (New York, NY, USA) [ 5 ]. Weeks later, other vaccines came out, and by the first trimester of 2021, several countries began to massively vaccinate their population [ 6 , 7 ] ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation